Ranirestat (AS-3201), a Potent Aldose Reductase Inhibitor, Reduces Sorbitol Levels and Improves Motor Nerve Conduction Velocity in Streptozotocin-Diabetic Rats - Takafumi Matsumoto; Yoshiyuki Ono; Masuo Kurono; Akemi Kuromiya; Keiji Nakamura; Vera Bril (Elsevier, 2008)
Ranirestat (AS-3201) is a novel aldose reductase (AR) inhibitor with potentially beneficial effects on diabetic sensorimotor polyneuropathy. In this study, we performed a kinetic analysis to determine the mode of inhibition of ranirestat on AR and investigated the effects of ranirestat on sorbitol levels in the sciatic nerves and lens of streptozotocin (STZ)-diabetic rats. We also evaluated the effects on motor nerve conduction velocity (MNCV) in STZ-diabetic rats. Kinetic analyses revealed that the ranirestat inhibition of AR is uncompetitive and reversible. In the sciatic nerve and lens of STZ-diabetic rats, single oral administration of ranirestat slightly reduced sorbitol levels. However, repeated oral administration of ranirestat for 5, 21, or 60 days enhanced the reducing effect of the ranirestat on sorbitol levels in the sciatic nerves and lens of STZ-diabetic rats with maximum effects after 21 days of treatment. Finally, repeated oral administration of ranirestat for 21 or 42 days dose-dependently improved the STZ-induced decrease in MNCV in STZ-diabetic rats. These findings demonstrate that repeated oral administration of ranirestat reduces sorbitol accumulation and improves MNCV in STZ-diabetic rats, indicating that ranirestat is an agent for the management of diabetic sensorimotor polyneuropathy. Keywords:: aldose reductase inhibitor, ranirestat (AS-3201), polyol pathway, motor nerve conduction velocity, streptozotocin-diabetic rat